LANGUAGE SKILLS AND SUCCESSFUL MISSION OF UN PEACEKEEPERS: A CASE STUDY OF ACEHNESE POLICEWOMEN - Mamadou Pouye; Ali Maksum (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
UN peacekeeping operations rely on international cooperation to constitute competitive female peacekeepers. Meanwhile, Indonesia is an active contributor to global peace, yet its women peacekeepers dealt with linguistic challenges to participate in peacekeeping missions in French-speaking countries. This article investigates the exhaustive intellectual and physical performances of a policewoman from Banda Aceh to take part in the MINUSCA ( United Nations Multidimensional Integrated Stabilization Mission in the Central African Republic) 2020-2021. This paper aims to illustrate the theory of feminism by using a descriptive qualitative analysis. In UN peacekeeping missions, having female peacekeepers is crucial for ensuring gender-balanced representation. This study describes how the determinism of the female gender through personal commitment, self-engagement, and motivation is as valuable as the male gender. The data are collected via recorded Zoom meetings. The findings revealed the components of French language proficiency for MINUSCA, learning activities, the Indonesian policewoman’s experiences in learning French, and French language teaching andlearning issues that needed to be addressed in Banda Aceh. In addition, this article underlines factual issues on the absence of an official French language academy in Banda Aceh. Addressing those issues will contribute to maximizing Indonesian human resources for global peace.